Quantitative trait locus mapping reveals an independent genetic basis for joint divergence in leaf function, life‐history, and floral traits between scarlet monkeyflower (Mimulus cardinalis) populations. Issue 5 (25th May 2021) - Nelson, Thomas C.; Muir, Christopher D.; Stathos, Angela M.; Vanderpool, Daniel D.; Anderson, Kayli; Angert, Amy L.; Fishman, Lila
Abstract : Premise: Across taxa, vegetative and floral traits that vary along a fast‐slow life‐history axis are often correlated with leaf functional traits arrayed along the leaf economics spectrum, suggesting a constrained set of adaptive trait combinations. Such broad‐scale convergence may arise from genetic constraints imposed by pleiotropy (or tight linkage) within species, or from natural selection alone. Understanding the genetic basis of trait syndromes and their components is key to distinguishing these alternatives and predicting evolution in novel environments. Methods: We used a line‐cross approach and quantitative trait locus (QTL) mapping to characterize the genetic basis of twenty leaf functional/physiological, life history, and floral traits in hybrids between annualized and perennial populations of scarlet monkeyflower ( Mimulus cardinalis ). Results: We mapped both single and multi‐trait QTLs for life history, leaf function and reproductive traits, but found no evidence of genetic co‐ordination across categories. A major QTL for three leaf functional traits (thickness, photosynthetic rate, and stomatal resistance) suggests that a simple shift in leaf anatomy may be key to adaptation to seasonally dry habitats. Conclusions: Our results suggest that the co‐ordination of resource‐acquisitive leaf physiological traits with a fast life‐history and more selfing mating system results from environmental selection rather than functional or genetic constraint. Independent assortment of distinct trait modules, as well as a simple genetic basis to leaf physiological traits associated with drought escape, may facilitate adaptation to changing climates.